Features of systemic lupus erythematosus in mice injected with bacterial lipopolysaccharides: identificantion of circulating DNA and renal localization of DNA-anti-DNA complexes (The Rockefeller University Press, 1977)
After injection of lipopolysaccharides (LPS) in mice, there is first a release of DNA into plasma and secondly an induction of anti-DNA antibodies. The circulating DNA was purified from plasma and physico- immunochemically characterized. This DNA has a similar density to mammalian cellular DNA,is 4--6S insize, and probably represents a mixture of single-stranded DNA (SSDNA) and double-stranded DNA (DSDNA) or DSDNA with some single-stranded regions. This purified DNA was shown to react with anti-DNA antibodies which appeared as early as 3 days after a single injection of LPS in mice. In serum, DNA-anti-DNA complexes were not detected, although unidentified circulating immune complex-like material was demonstrated 5-8 days after the injection of LPS. In tissues, particularly in renal glomeruli, fine granular immune complex-type immunoglobulin deposits appeared along the glomerular capillary walls and in the mesangium 3 days after the injection of LPS. There is a direct correlation between the level of anti-DNA antibodies and the intensity of glomerular deposits and about 40% of immunoglobulins eluted from kidneys are anti-DNA antibodies, indicating that some of the immune complexes localized in kidneys are DNA-anti-DNA complexes. Based on these observations, the following hypothetical mechanism for the glomerular localization of DNA-anti-DNA complexes after the injection of LPS in mice is proposed. First, DNA, which has been released in circulating blood after injection of LPS, might bind to renal glomeruli, probably on glomerular basement membranes (GBM) through a high affinity of GBM for DNA; secondly, circulating anti-DNA antibodies, which appear later, might react with the glomerular-bound DNA and form immune complexes independently of circulating immune complexes. However, the possibility of direct deposition of immune complexes is not ruled out.